2020
DOI: 10.1016/j.amsu.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Surgical application of the keystone island flap for closure of thoracolumbar myelomeningocele defects - A case report

Abstract: Introduction Myelomeningocele (MMC) is the most common neural tube defect that can occur due to neural tube's failure to fuse properly during embryonic life. To prevent this, keystone island flap can be used for closure of large MMCs. Presentation of case A new-born girl born as a product of 36 weeks of gestation had a weight of 3.020 kg and had multiple congenital anomalies including hydrocephalus, thoracolumbar myelomeningocele at the level of (T10-L4) and an atrial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Eight previous studies have discussed the use of KDPIFs for meningomyelocele defect closure [15,[18][19][20][21][22][23][24]. All of those studies also demonstrated satisfactory experiences in using KDPIFs for meningomyelocele closure.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Eight previous studies have discussed the use of KDPIFs for meningomyelocele defect closure [15,[18][19][20][21][22][23][24]. All of those studies also demonstrated satisfactory experiences in using KDPIFs for meningomyelocele closure.…”
Section: Discussionmentioning
confidence: 93%
“…All of those studies also demonstrated satisfactory experiences in using KDPIFs for meningomyelocele closure. The studies by Gutman et al [15], Park et al [19], Jamjoom et al [20], Mrad et al [21], and Gomez and Barrera [22] reported no complications after defect closure using keystone flaps in between one and five patients. Donaldson et al [18] reported that two out of six patients had wound complications after surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Putri et al 18 concluded that smaller defects (<15 cm²) tend to be closed with type II KDPIF, and larger defects (>30 cm²) are more often closed with bilateral type IV KDPIF. Mrad et al 19 proved that KDPIF is effective for locoregional fasciocutaneous reconstruction of large thoracolumbar MMC defects. An intercostal artery island flap has also been used to repair a huge lumbosacral MMC defect, 20 so an abdominal island flap does, 21 both of them can achieve repairment of defect which is limited by area.…”
Section: Discussionmentioning
confidence: 99%
“…1). 3,5,6,8,[12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In addition, a retrospective chart review of all MMC closures performed at Phoenix Children's Hospital from January 2015 to January 2020. After proper IRB approval, all closures performed by board-certified plastic surgeons were identified and further analyzed.…”
Section: Methodsmentioning
confidence: 99%